2015
DOI: 10.26719/2015.21.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sustainability of zero central-line associated bloodstream infections is possible with high compliance with care bundle elements

Abstract: Central-line-associated bloodstream infection (CLABSI) is one of the most important problems in intensive care units (ICUs) worldwide. A bundle of CLABSI care measures was introduced at a 13-bed medical/ surgical ICU in Kocaeli, Turkey in January 2010. Compliance rates with the bundle were measured at the beginning of the third quarter of 2010 until June 2013 and compared with CLABSI rates. During the post-intervention period, of 2196 ICU patients, 732 lines placed for 4366 line-days were monitored. Feedback t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 20 publications
0
20
0
1
Order By: Relevance
“…CLABSI rate prior to introduction of care bundle at one hospital was reported to be 12.8/1000 catheter days. Over time, following implementation of the intervention and with judicious process evaluation and monitoring, the infection rate was reported as 0 for a 3-year time period [25]. The authors of the study mentioned that a ''culture of safety'' was related to their success with this program.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…CLABSI rate prior to introduction of care bundle at one hospital was reported to be 12.8/1000 catheter days. Over time, following implementation of the intervention and with judicious process evaluation and monitoring, the infection rate was reported as 0 for a 3-year time period [25]. The authors of the study mentioned that a ''culture of safety'' was related to their success with this program.…”
Section: Discussionmentioning
confidence: 97%
“…While the full extent of the financial burden of wound complications following VIHR is not in the scope of this study, quantifying the complete costs of wound complications is needed to define the comprehensive financial impact of VIHR to patients, hospitals, and society. Because of the high incidence, morbidity, and excess utilization of resources associated with central line-associated bloodstream infections (CLABSI), care bundles aimed at reducing the infection rate to near-zero have been introduced in health care systems [25,26]. CLABSI rate prior to introduction of care bundle at one hospital was reported to be 12.8/1000 catheter days.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bundles can be defined as the systematic implementation of a set of evidence-based practices, usually three to five, that when performed properly and collectively can improve patient outcomes. Research on CRBSI prevention demonstrated the effectiveness of bundles, which reduce the incidence of CRBSI by up to 80% [35][36][37], reaching a rate of 0 in some cases [38]. Education and training of healthcare workers and adherence to standardized protocols for insertion and maintenance of intravascular catheters significantly reduced the incidence of catheter-related infections and represent the most important preventive measures.…”
Section: Healthcare-associated Infections and Patient Safetymentioning
confidence: 99%
“…Santral kateter ilişkili kan dolaşımı enfeksiyon insidansını, YBÜ'lerin kapasitesi, iş yükü, hastaların alt hastalıkları, mevcut hastalığın ağırlığı gibi faktörler belirlemektedir [27] . Ancak, yapılan çalışmalarda enfeksiyon kontrol demet uygulamaları ile SKİ-KDE hızının sıfıra indirilebileceği gösterilmiştir [28,29] .…”
Section: Santral Kateter İlişkili Kan Dolaşımı Enfeksiyonu öNleme Demetiunclassified